Voices of Ahmad Dahlan University English Literature Students regarding the Use of YouTube in Teaching English - Kusdaryono, Junianto Bayu; Ananta Tur, Ajar Pradika; Pratolo, Bambang Widi (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
This qualitative study investigates the perspectives of English literature students at Ahmad Dahlan University regarding the use of YouTube as a teaching medium for English. The aim of this research is to understand the strengths and weaknesses of YouTube as a platform for teaching English through the voices of the students. Through semi-structured interviews, the study explores the students' perceptions of the benefits and drawbacks of using YouTube for English language instruction. The findings reveal that while most students support YouTube for English teaching due to its accessibility and visual/auditory learning, some express concerns about distractions and lack of real-time feedback. Students suggest strategies like incorporating animations, selecting high-quality content, and utilizing interactive features. Previous research also supports the positive perception of using YouTube for English language instruction, with references provided.